Family and gender still matter: the heterogeneity of returns to education in Germany - Reinhold Schnabel; Isabel Schnabel (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2002)
Using information on family background, we estimate returns to education, allowing for the heterogeneity of returns. In order to control for the unobserved heterogeneity shared by family members, we construct a siblings sample and employ family fixed-effects and family correlated random-effects models. Our main result is that family background still matters despite the substantial political efforts to equalize educational opportunities in Germany. Persons with less-educated parents earn lower wages, but have higher returns to education. This supports the view that persons from less-educated backgrounds still face higher marginal costs in the educational system. The same interplay between the wage level and marginal returns is found for the effect of gender and cohort.
Keywords: J31; C23; 330; Returns to education; siblings analysis; heterogeneity of returns; Bildungsertrag; Bildungsniveau; Familiensoziologie; Geschlecht; Bildungschancen; Schätzung; Deutschland